Analysis of cascaded H-bridge multilevel inverter with current control methods - Prem Sunder Gnanamurthy; Veerapathiran Govindasamy (Institute of Advanced Engineering and Science, 2022)
A detailed model and analysis of a five-level cascaded H-bridge (CHB) multilevel inverter with different current control methods are presented. Simulation models of the CHB inverter with hysteresis current controller, PI current controller using SPWM technique and predictive current controller have been built to demonstrate the CHB inverter system performance with regard to load current THD and reference current tracking. In controlling the load current, the hysteresis and the PI current controllers have the problem of current ripple and phase lag, respectively. The proposed predictive current control method effectively addresses these issues. The current control methods are analyzed for varying reference current and unbalanced load conditions. The simulation results are observed and analyzed using the MATLAB Simulink software to validate the current control methods.